2019
DOI: 10.1016/j.joco.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of iris color and its association with ocular diseases in a rural population of Iran

Abstract: PurposeTo determine the distribution of iris color and its relationship with some ocular diseases in a rural population of Iran.MethodsTwo rural areas of the north and southwest of Iran were selected by a cross-sectional study using multi-stage cluster sampling. After selecting samples, the participants had an eye examination including measuring visual acuity, refraction, and Pentacam imaging. Then an eye examination for individuals was performed by slit-lamp.ResultsOut of 3851 invited people, 3314 participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…More than 90% had dark brown and medium brown eyes, and nearly one-tenth of the subjects had light eyes (light brown, yellow or green, and gray or blue). Our study findings were quite consistent with the findings of other studies in Iran such as that by Hashemi et al (23), who reported medium brown as the most common eye color in their study in Tehran in 2010 (in Hashemi et al study: 54.09% and in our study: 49.50%) However, our results are significantly different from studies in other countries. Studies on European subjects (5,19).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…More than 90% had dark brown and medium brown eyes, and nearly one-tenth of the subjects had light eyes (light brown, yellow or green, and gray or blue). Our study findings were quite consistent with the findings of other studies in Iran such as that by Hashemi et al (23), who reported medium brown as the most common eye color in their study in Tehran in 2010 (in Hashemi et al study: 54.09% and in our study: 49.50%) However, our results are significantly different from studies in other countries. Studies on European subjects (5,19).…”
Section: Discussionsupporting
confidence: 89%
“…Based on the results of this study and other studies conducted around the world, it may be argued that the difference in iris color is due to two reasons: first, the method used in our study and Hashemi's study (23), is different from the method used in studies in some other countries (5,9,11,12,19,20), which can justify part of the difference. The second reason, which is the more important reason, is genetic factors.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…24 A study of a Middle-Eastern population noted more than 50% of the normal adult population had dark brown irides. 25 The proportion of iris colours is unknown in the Saudi population. Therefore, authors recommend further research on role of laser PI in an Arab population to address damage to posterior segment due to PACG.…”
Section: Discussionmentioning
confidence: 99%
“…The methodology of the study was explained in detail elsewhere. 25 26 First, the list of all underserved districts in Iran was provided, and then two were randomly selected in the north (Kojur District, Mazandaran Province) and southwest of Iran (Shahyun District, Khuzestan Province) using national data. Then, using the list of all villages in these districts, 15 villages from Shahyun and 5 villages from Kojur were selected randomly.…”
Section: Ethodsmentioning
confidence: 99%